Kesiapan Kerja Calon Akuntan di Era Pandemi Covid-19 - Erawan, Ni Made Ayu Nirmalasari Putri; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 32 No 4 (2022)DO - 10.24843/EJA.2022.v32.i04.p15, 2022)
The purpose of this study was to analyze the factors of accounting expertise, new literacy, and motivation on the job readiness of prospective accountants in the Covid-19 pandemic era. This research was conducted at Universities spread across Bali which have A & B accredited Accounting Study Programs in 2021. The number of samples used was 93. Data was collected by distributing questionnaires. The data analysis technique in this study used multiple linear regression analysis with the Smart-PLS tool. The results of the study prove that Accounting Skills have a positive and significant effect on job readiness. New Literacy has a positive and significant effect on job readiness. Motivation has a positive and significant effect on accounting expertise on job readiness. Motivation has a negative and insignificant effect with new literacy on work readiness.          Keywords: Accounting Skills; New Literacy; Motivation; Working Readiness.